Physical therapy and early mobilization in the adult intensive care unit: Historical context, concepts and public policies - Camilo, Richardson Morais; Barbosa, Roberta Ribeiro Batista; Oliveira, Fernando Rocha (Seven Editora, 2024)
Immobility in critically ill patients can generate complications that affect recovery, such as muscle atrophy and skeletal weakness, causing a burden both for patients and for the Unified Health System (SUS). The consequences of immobility can persist for up to five years after hospital discharge, characterizing a public health problem, as it increases comorbidities, mortality rates, and the frequency of need for high-complexity care, overloading both families and the Brazilian health system. Thus, the objective of this study was to review the narrative literature on the benefits of PM in the ICU, aiming to improve the understanding of this topic, with a potential positive impact on patient care, highlighting the importance of public policies applied to this area. It is noteworthy that physiotherapy and Early Mobilization (PM) in the Intensive Care Unit (ICU) can contribute to mitigate the effects of immobility. However, the implementation of early mobilization faces challenges due to the lack of clear guidelines and institutional barriers, which can result in reduced quality of life, difficulties in the patient’s social and professional reintegration, and generate significant financial costs. The Additional Cost and Utilization of Resources after critical hospitalizations mainly affects young people without comorbidities, resulting in economic impacts and challenges for the health system. The Unified Health System (SUS) plays a crucial role in mediating the demand for physiotherapy and the supply of services, although it faces obstacles in promoting the physical and functional health of the Brazilian population. DOI:https://doi.org/10.56238/sevened2024.001-010